1975
DOI: 10.1159/000149933
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Infection of Human Lung Epithelial Cells <i>in vitro</i>

Abstract: Human lung epithelial cells were productively infected with human cytomegalovirus in vitro. Infectious virus was released up to 8 weeks postinfection. The cells retained their morphological characteristics throughout the period of observation, while simultaneously bearing all the features typical of cytomegalovirus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…2A and data not shown). Several reports have demonstrated syncytium formation by HCMV clinical isolates in fibroblasts and epithelial cells (5,30,42), and the phenotype of the repaired AD169 derivative indicates that the UL131 product is needed for cell-cell fusion. The formation of syncytia would mediate cell-to-cell spread of HCMV while allowing it to evade neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2A and data not shown). Several reports have demonstrated syncytium formation by HCMV clinical isolates in fibroblasts and epithelial cells (5,30,42), and the phenotype of the repaired AD169 derivative indicates that the UL131 product is needed for cell-cell fusion. The formation of syncytia would mediate cell-to-cell spread of HCMV while allowing it to evade neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the frequent and extensive infection of epithelial cell populations by HCMV in vivo, only a few cultured epithelial cells have been reported to be susceptible to HCMV infection, including primary lung epithelial cells (30), thyroid epithelial cells (26), HCMC and Caco-2 epithelial cells derived from colon (24,40), cervical epithelial cells (41), and BAMB cells derived from amniotic fluid cells (42). However, most analyses of HCMV epithelial cell tropism have been performed using laboratory-adapted strains, and potential variations among virus strains were not taken into consideration.…”
mentioning
confidence: 99%
“…In vitro, however, full productive infection is supported only in secondary cell strains of fibroblasts and endothelial cells, in fully differentiated myeloid cells, and in primary cultures of hepatocytes and lung epithelial cells (Michelson-Fiske et al, 1975;Sinzger et al, 1995Sinzger et al, , 1999Plachter et al, 1996). We demonstrated here that human adrenocortical cell lines are fully permissive for infection and replication not only by fibroblast-adapted laboratory HCMV strains but also by clinical isolates of HCMV.…”
Section: Discussionmentioning
confidence: 72%
“…6E). Given the inherent difficulties in studying virus pathogenesis in human lung, the sole study of HCMV infection in alveolar epithelial cells in vitro was reported more than 3 decades ago (42). Much of our knowledge about the special role of the lung in CMV pathogenesis thus comes from studies of murine CMV (MCMV) infection, where the lung was identified as a major site of MCMV latency and reactivation (4).…”
Section: Discussionmentioning
confidence: 99%